Tatak Pilipino [episode no. 38 & 39]. ([Quezon City ABS-CBN, 1991)
A unique display of Pilipino ways and style.
Male wearing earrings (15 min.) -- Menstruation feature (15 min.) -- Sa kabilang banda featuring Regine Velasquez and her art (10 min.) -- Simbahang kalikasan (5 min.) -- Balagtasan feature on U. S. military bases (15 min.)
In English and Pilipino.
Hosts, Jim Paredes and Gel Santos Relos.
Keywords: Velasquez, Regine; Menstruation -- Folklore; Earrings -- Philippines; Balagtasan; Military bases, American; Immaculate Parish Church (Las Pinas, Rizal).